Tomographic presentation with miliary appearance in an immunocompromised patient with pulmonary candidiasis: A case report - Luis Alejandro Rodríguez-Hidalgo; Diana Cecilia Ruiz-Caballero; César Augusto Colunche-Narváez; Amalia Guadalupe Vega-Fernández; Theresina Elizabeth Rodríguez-Sáenz (Medwave)
Introduction Candida albicans infection shows a wide range of patterns on chest computed tomography, including ground glass opacities and consolidation, with the miliary pattern being the least frequent. The miliary pattern is not exclusive to tuberculosis. Fungal lung infections are rare and potentially fatal. Colonization by Candida albicans, associated with impaired immunity, requires early empirical antifungal therapy to improve survival.